Characterization of ibrutinib‐sensitive and ‐resistant mantle lymphoma cells. (24th June 2014) - Ma, Jiao; Lu, Pin; Guo, Ailin; Cheng, Shuhua; Zong, Hongliang; Martin, Peter; Coleman, Morton; Wang, Y. Lynn
Summary Ibrutinib inhibits Bruton tyrosine kinase (BTK), a key component of early B‐cell receptor (BCR) signalling pathways. A multicentre phase 2 trial of ibrutinib in patients with relapsed/refractory mantle cell lymphoma (MCL) demonstrated a remarkable response rate. However, approximately one‐third of patients have primary resistance to the drug while other patients appear to lose response and develop secondary resistance. Understanding the molecular mechanisms underlying ibrutinib sensitivity is of paramount importance. In this study, we investigated cell lines and primary MCL cells that display differential sensitivity to ibrutinib. We found that the primary cells display a higher BTK activity than normal B cells and MCL cells show differential sensitivity to BTK inhibition. Genetic knockdown of BTK inhibits the growth, survival and proliferation of ibrutinib‐sensitive but not resistant MCL cell lines, suggesting that ibrutinib acts through BTK to produce its anti‐tumour activities. Interestingly, inhibition of ERK1/2 and AKT, but not BTK phosphorylation per se, correlates well with cellular response to BTK inhibition in cell lines as well as in primary tumours. Our study suggests that, to prevent primary resistance or to overcome secondary resistance to BTK inhibition, a combinatory strategy that targets multiple components or multiple pathways may represent the most effective approach.